Differences between inferior and superior bulbar conjunctiva goblet cells in scleral lens wearers: a pilot study - Macedo-de-Araújo, Rute J.; Serramito-Blanco, Maria; Van der Worp, Eef; Carracedo, Gonzalo; González-Méijome, José Manuel (Optometry and vision science, 2020)
Significance: Scleral lenses (SLs) rest on the scleroconjunctival region, which could result in a mechanical impact in the bulbar conjunctiva that can hypothetically modify some properties of conjunctival cells.PURPOSE: The purpose of this study was to evaluate the differences in goblet cell density (GCD) andmucin cloud amplitude (MCA) between superior and inferior bulbar conjunctiva in SL wearers.METHODS: A total of 26 eyes wearing SL were randomly selected from 26 subjects (11 females) with different grades of keratoconus enrolled in a prospective clinical series. Superior and inferior conjunctival impression cytologies were performed and therefore analyzed with scanning laser confocal microscopy to evaluate GCD and MCA. All subjects filled out the Ocular Surface Disease Index (OSDI) questionnaire.RESULTS: The mean +/- standard deviation OSDI score was 23.62 +/- 15.12. Although a higher density of goblet cells was observed in the samples taken in the superior conjunctiva (74.70 +/- 57.55 cells/mm(2)) than on the inferior conjunctiva (55.91 +/- 34.80 cells/mm(2)), there were no statistically significant differences between them (P = .14, Wilcoxon). Regarding MCA, no differences were found between superior (21.81 +/- 3.30 mu m) and inferior (20.72 +/- 2.95 mu m) samples (P = .201, Wilcoxon). No statistically significant differences were found in GCD and MCA regarding the time of SL wear.CONCLUSIONS: There were no differences in GCD and MCA in the samples taken in the superior and inferior conjunctival areas. Also, it seems that the SL wearing time does not affect the density and secretion of goblet cells. Prospective studies need to be conducted in larger samples to confirm those outcomes. Bausch & Lomb (to RJM-d-A). PTDC/SAU-BEB/098391/ 2008, PTDC/FIS-OPT/0677/2014 and the Strategic Funding UID/FIS/04650/2013